Insightful health assessment of paediatric hemato-oncology patients’ well-being through knowledge and attitude survey of their caretakers: A hospital-based study - Miria Aingel Cherian; Nirali Dilip Patil; Manjula Gudhoor; Rhea Simon; Soukhya Kapsi; Abhilasha Sampagar; Madiwalayya S. Ganachari (İstanbul Journal of Pharmacy)
Background and Aim: Cancer is a potentially fatal disease that is characterized by aberrant cell prolifer. ation that spreads and eventually causes the death of the cells. Well. being has been an intricate and distressing obstacle in oncology and is one of the most concerning health issues for cancer patients. The emotional and psychological toll on both the child and their family is equally substantial, as the journey through diagnosis, treatment, and recovery is often marked by fear, uncertainty, and distress. The purpose of the current study was to measure the overall general well.being of paediatric hemato. oncology patients. Methods: The project was conducted in paediatric hemato.oncology department. In this study, self. developed validated questionnaires were used for the patient’s caretakers regarding their child’s overall well.being. Results: The study found that the patient caretaker’s opinion and understanding about the illness varies significantly from research to study. A statistical investigation showed that a significant number of caretakers (55.5%) were more aware about the disease. Additionally, there were considerable differences in the attitudes of caretakers regarding the condition; among them (84.7%) disagreed with the statement “Once you’ve had cancer, you can never be normal again”, showcasing a positive and informed attitude. Conclusion: Enhancing the quality of life for paediatric cancer patients involves comprehensive care, including medical, psychological and social support, pain management and holistic care. Continued research and advocacy are essential to provide hope, comfort, and opportunities for a fulfilling childhood despite cancer’s challenges.